Corak Tafsir Aqidah (Kajian Komparatif Penafsiran Ayat-ayat Aqidah) - Ahmad Atabik (Esensia: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
This article seeks to describe the theological genre of Qur’anic exegesis with special reference to the comparative sudy on various Qur’anic exegesis towards theological verses. In the course of kalām (theology), there are plenty of  Islamic sects, those who involved in the debate of disputed theological issues, most notable of them are the Ash’arite and the Mu’tazilite. Their contention concerning theological issues has also affected the mufassir (Qur’anic exegetes), those who interpret the Qur’anic verses. Some problems which are previously not taken into consideration, gradually systematized, conceived, polarized, and even cause the contention among Islamic community. In this paper, i describe and analyze two issues on kalām discourse; the word of God (kalām Allāh) and ru’yatullāh (seeing God in heaven). In the disputes on both issues, i also provide the Qur’anic exegesis from Mu’tazilite, Asy’arite, and Salafi-Wahabi.